House Prices, Home Equity–Based Borrowing, and the US Household Leverage Crisis - Mian, Atif; Sufi, Amir (American Economic Review, 2011)
Borrowing against the increase in home equity by existing homeowners was responsible for a significant fraction of the rise in US household leverage from 2002 to 2006 and the increase in defaults from 2006 to 2008. Instrumental variables estimation shows that homeowners extracted 25 cents for every dollar increase in home equity. Home equity–based borrowing was stronger for younger households and households with low credit scores. The evidence suggests that borrowed funds were used for real outlays. Home equity–based borrowing added $1.25 trillion in household debt from 2002 to 2008, and accounts for at least 39 percent of new defaults from 2006 to 2008. JEL: D14, R31